KELIMPAHAN PLANKTON DAN PEMANFAATANNYA OLEH NILA MERAH (Oreochromis sp.) DALAM HAPA PEMBENIHAN DAN PENDEDERAN DI WADUK SERMO - Rustadi Rustadi (Universitas Gadjah Mada, 2008)
Plankton monitoring were conducted in hatchery and rearing hapas of red tilapia (Oreochromis sp.) to know plankton abundance and its utilization by fish during 98 days. Be-weekly plankton samples and fry fish guts were taken from fish hapa rearing, meanwhile brood fish gut were taken monthly. Be-weekly plankton and water monitoring were also applied in fish rearing without feed, water outside of hapas and river. Two units of bamboo frame, 6 x 6 m2 divided into 4 blocks respectively, were used for fixing 2 x 3 x 1 m3 hatchery hapa, and 1 x 2 x 1 m3 rearing hapa. Commercial feed was given daily to brood stock at the rate of 2% of the total fish weight and fry at the rate of 40%. Plankton density and composition in hatchery and rearing hapas were higher density than water reservoir and river. All size of red tilapia consumed selected plankton species, about 31.34-38.89% of existing species. Dominant plankton in hapa water were: Navicula, Closteriopsis, Sphaerocystis, Surirella dan Arthrodesmus and among them were prefered by red tilapia as natural food, namely Navicula, Surirella, Closteriopsis dan Sphaerocystis. Water quality parameters were still suitable for fish growth and breeding, but dissolved oxygen tended to low due to high plankton abundance.